2017
DOI: 10.3906/mat-1602-25
|View full text |Cite
|
Sign up to set email alerts
|

Second Hankel determinant for certain subclasses ofbi-univalent functions

Abstract: In the present paper, we obtain the upper bounds for the second Hankel determinant for certain subclasses of analytic and bi-univalent functions. Moreover, several interesting applications of the results presented here are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Very recently, the upper bounds of H 2 (2) for the classes S * σ (β) and K σ (β) were discussed by Deniz et al [14]. Later, the upper bounds of H 2 (2) for various subclasses of σ were obtained by Altınkaya and Yalçın [6,7], Ç aglar et al [11], Kanas et al [22] and Orhan et al [32] (see also [28,33]).…”
Section: Introduction and Definitionsmentioning
confidence: 99%
“…Very recently, the upper bounds of H 2 (2) for the classes S * σ (β) and K σ (β) were discussed by Deniz et al [14]. Later, the upper bounds of H 2 (2) for various subclasses of σ were obtained by Altınkaya and Yalçın [6,7], Ç aglar et al [11], Kanas et al [22] and Orhan et al [32] (see also [28,33]).…”
Section: Introduction and Definitionsmentioning
confidence: 99%
“…for some x, y, s, t with |x| ≤ 1, |y| ≤ 1, |s| ≤ 1 and |t| ≤ 1. Applying (16) and (17) in (15), it follows that…”
Section: Proof Of Theorem 2 As Noted Inmentioning
confidence: 99%
“…In recent years, the research on Hankel determinants has focused on the estimation of |H 2 (2)|. Problems in this field has also been argued by several authors for various classes of univalent functions [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Srivastava and his coauthors [21] found the estimate of the second Hankel determinant for bi-univalent functions involving the symmetric q-derivative operator, while in [22], the authors studied Hankel and Toeplitz determinants for subfamilies of q-starlike functions connected with the conic domain. For more literature, see [23][24][25][26][27][28][29][30].…”
Section: Introduction and Definitionsmentioning
confidence: 99%